Admission profile and discharge outcomes for infants aged less than 6 months admitted to inpatient therapeutic care in 10 countries. A secondary data analysis. Issue 3 (25th July 2016) - Grijalva‐Eternod, Carlos S.; Kerac, Marko; McGrath, Marie; Wilkinson, Caroline; Hirsch, June C.; Delchevalerie, Pascale; Seal, Andrew J.
Abstract: Evidence on the management of acute malnutrition in infants aged less than 6 months (infants <6mo) is scarce. To understand outcomes using current protocols, we analysed a sample of 24 045 children aged 0–60 months from 21 datasets of inpatient therapeutic care programmes in 10 countries. We compared the proportion of admissions, the anthropometric profile at admission and the discharge outcomes between infants <6mo and children aged 6–60 months (older children). Infants <6mo accounted for 12% of admissions. The quality of anthropometric data at admission was more problematic in infants <6mo than in older children with a greater proportion of missing data (a 6.9 percentage point difference for length values, 95% CI: 6.0; 7.9, P  < 0.01), anthropometric measures that could not be converted to indices (a 15.6 percentage point difference for weight‐for‐length z‐score values, 95% CI: 14.3; 16.9, P  < 0.01) and anthropometric indices that were flagged as outliers (a 2.7 percentage point difference for any anthropometric index being flagged as an outlier, 95% CI: 1.7; 3.8, P  < 0.01). A high proportion of both infants <6mo and older children were discharged as recovered. Infants <6mo showed a greater risk of death during treatment (risk ratio 1.30, 95% CI: 1.09; 1.56, P  < 0.01). Infants <6mo represent an important proportion of admissions to therapeutic feeding programmes, and there are crucial challenges associated with their care. Systematic compilation and analysis of routine data for infants <6mo is necessary for monitoring programme performance and should be promoted as a tool to monitor the impact of new guidelines on care.